The Bible and the pursuit of happiness : what the Old and New Testaments teach us about the good life - Strawn, Brent A. (Oxford University Press, 2013)
Scholars of the social sciences have devoted more and more attention of late to the concept of human happiness, mainly from sociological and psychological perspectives. This volume, which includes essays from scholars of the New Testament, the Old Testament, systematic theology, practical theology, and counseling psychology, poses an exciting question: what is happiness according to the Bible?